2019
DOI: 10.1084/jem.20190344
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the interleukin-6 receptor causes immunodeficiency, atopy, and abnormal inflammatory responses

Abstract: IL-6 excess is central to the pathogenesis of multiple inflammatory conditions and is targeted in clinical practice by immunotherapy that blocks the IL-6 receptor encoded by IL6R. We describe two patients with homozygous mutations in IL6R who presented with recurrent infections, abnormal acute-phase responses, elevated IgE, eczema, and eosinophilia. This study identifies a novel primary immunodeficiency, clarifying the contribution of IL-6 to the phenotype of patients with mutations in IL6ST, STAT3, and ZNF341… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
128
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 34 publications
5
128
0
2
Order By: Relevance
“…This observation is consistent with the near-normal counts of Th17 cells in the patients described here, at odds with the data for patients with STAT3 mutations (Milner et al, 2008;Ma et al, 2008Ma et al, , 2015Ma et al, , 2016de Beaucoudrey et al, 2008). Near-normal Th17 cell levels and a lack of CMC were observed in patients with biallelic null mutations of IL6R, IL23R, or IL21R (Kotlarz et al, 2013;Martínez-Barricarte et al, 2018;Spencer et al, 2019;Ma et al, 2016). This suggests that IL-6R, IL-21R, and IL-23R are individually, but not collectively, redundant for Th17 cell differentiation, accounting for CMC in patients with DN STAT3 or AR ZNF341 deficiency, whose cellular responses to IL-6, IL-21, and IL-23 are all impaired.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation is consistent with the near-normal counts of Th17 cells in the patients described here, at odds with the data for patients with STAT3 mutations (Milner et al, 2008;Ma et al, 2008Ma et al, , 2015Ma et al, , 2016de Beaucoudrey et al, 2008). Near-normal Th17 cell levels and a lack of CMC were observed in patients with biallelic null mutations of IL6R, IL23R, or IL21R (Kotlarz et al, 2013;Martínez-Barricarte et al, 2018;Spencer et al, 2019;Ma et al, 2016). This suggests that IL-6R, IL-21R, and IL-23R are individually, but not collectively, redundant for Th17 cell differentiation, accounting for CMC in patients with DN STAT3 or AR ZNF341 deficiency, whose cellular responses to IL-6, IL-21, and IL-23 are all impaired.…”
Section: Discussionsupporting
confidence: 90%
“…Collectively, these findings suggest that many, perhaps even most, of the immunological abnormalities seen in patients with STAT3 deficiency, whether biological (high IgE levels), clinical (atopy and recurrent staphylococcal infections), or both (low levels of inflammation), are due to poor cellular responses to IL-6 (Puel and Casanova, 2019), whereas most of the skeletal abnormalities are due to poor responses to IL-11 (craniosynostosis and deciduous tooth retention) or LIF (scoliosis, osteoporosis). The apparent lack of CMC in patients with AR deficiency of IL-6R, IL-10RA, IL-10RB, IL-11R, IL-21R, IL-23R, IFNAR1, IFNAR2, LIF-R, or OSM-R deficiency (Schwerd et al, 2017;Spencer et al, 2019;Nieminen et al, 2011;Mikelonis et al, 2014;Arita et al, 2008;Martínez-Barricarte et al, 2018;Hernandez et al, 2019;Glocker et al, 2011;Kotlarz et al, 2014;Duncan et al, 2015) also suggested that the pathogenesis of impaired IL-17 immunity and CMC in patients with mutations in STAT3 or ZNF341 may involve the disruption of multiple cytokine responsive pathways (Minegishi et al, 2007;Puel et al, 2011;Béziat et al, 2018;Ma et al, 2016). We tested whether new genetic etiologies of AD-HIES could shed light on the pathogenesis of various individual HIES phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that multiple redundant pathways converge during the course of Th17 differentiation in vivo . Patients with IL‐6 receptor (IL‐6R) inactivating mutations have normal levels of circulating Th17 cells, but their development in vitro from naive precursors is affected . Hence, IL‐6 signaling deficiency alone in vivo can be substituted by other redundant factors.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with IL-6 receptor (IL-6R) inactivating mutations have normal levels of circulating Th17 cells, but their development in vitro from naive precursors is affected. 20 Hence, IL-6 signaling deficiency alone in vivo can be substituted by other redundant factors. In agreement with this, the frequency of peripheral CCR4 + CCR6 + Th17 cells is normal in patients with autosomal recessive IL23R deficiency, but they do not differentiate properly in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the findings of Spencer et al (2019) in two unrelated kindreds provide compelling genetic evidence that IL-6 is essential for host inflammatory defense against staphylococci and for the regulation of IgE-mediated allergy, including severe eczema in particular. Patients treated with IL-6 blockers for long periods should be carefully monitored for these side effects.…”
mentioning
confidence: 99%